IDENTIFICATION AND DETERMINATION OF 2,5-DIMETOXY-4-BROMOPHENETHYLAMINE (2C-B) IN REAL SAMPLE BY GC-MS METHODS AND DERIVATIZATION AFTER SPE PREPARATION - Lukić, Vera; Micić, Ružica; Radosavljević, Živana (Bulletin of Natural Sciences Research, 2022)
The abuse of new psychoactive substances is attracting a lot of attention from the world public. There is an increasing use among young people, who are not aware of the harmful effects of this substances. Some of these substances may have been around for years, but have reemerged in the market in altered chemical forms and launched as legal alternatives to common drugs of abuse. This paper describes application of gas chromatography coupled with mass spectrometry method (GC-MS) to identify 2,5-dimetoxy-4-bromophenethylamine (2C-B) compound in urine sample after solid phase extraxtion and derivatization with N-methyl-bis-trifluoroacetamide (MBTFA). Gas chromatographic separation of TFA derivative of 2C-B (2C-B TFA) was successfully performed using DB-5MS capillary column (5% diphenyl-95% dimethilsiloxane). Selected ion monitoring (SIM) technique was used for qvantitative analyses wich was performed using matrix mached calibratores, whereby good results were achieved. Urine sample wich contained 2C-B was obtained within International Quality Assurance Programme - International Collaborative Exercises (ICE) program organized by the scientific department of United Nations Office on Drugs and Crime (UNODC). The aim of this study was to develop a simple and sensitive method of gas chromatography mass spectrometry (GC-EI-MS) for the identification, extraction and quantitative analysis of 2C-B in the urine sample, which is near the blood remains a priority analyzed matrix in clinical and forensic toxicology.